Glycoprotein A33 deficiency: a new mouse model of impaired intestinal epithelial barrier function and inflammatory disease - Benjamin B. Williams; Niall C. Tebbutt; Michael Buchert; Tracy L. Putoczki; Karen Doggett; Shisan Bao; Cameron N. Johnstone; Frederick Masson; Frederic Hollande; Antony W. Burgess; Andrew M. Scott; Matthias Ernst; et al. (The Company of Biologists, 2015)
The cells of the intestinal epithelium provide a selectively permeable barrier between the external environment and internal tissues. The integrity of this barrier is maintained by tight junctions, specialised cell-cell contacts that permit the absorption of water and nutrients while excluding microbes, toxins and dietary antigens. Impairment of intestinal barrier function contributes to multiple gastrointestinal disorders, including food hypersensitivity, inflammatory bowel disease (IBD) and colitis-associated cancer (CAC). Glycoprotein A33 (GPA33) is an intestinal epithelium-specific cell surface marker and member of the CTX group of transmembrane proteins. Roles in cell-cell adhesion have been demonstrated for multiple CTX family members, suggesting a similar function for GPA33 within the gastrointestinal tract. To test a potential requirement for GPA33 in intestinal barrier function, we generated Gpa33−/− mice and subjected them to experimental regimens designed to produce food hypersensitivity, colitis and CAC. Gpa33−/− mice exhibited impaired intestinal barrier function. This was shown by elevated steady-state immunosurveillance in the colonic mucosa and leakiness to oral TRITC-labelled dextran after short-term exposure to dextran sodium sulphate (DSS) to injure the intestinal epithelium. Gpa33−/− mice also exhibited rapid onset and reduced resolution of DSS-induced colitis, and a striking increase in the number of colitis-associated tumours produced by treatment with the colon-specific mutagen azoxymethane (AOM) followed by two cycles of DSS. In contrast, Gpa33−/− mice treated with AOM alone showed no increase in sporadic tumour formation, indicating that their increased tumour susceptibility is dependent on inflammatory stimuli. Finally, Gpa33−/− mice displayed hypersensitivity to food allergens, a common co-morbidity in humans with IBD. We propose that Gpa33−/− mice provide a valuable model to study the mechanisms linking intestinal permeability and multiple inflammatory pathologies. Moreover, this model could facilitate preclinical studies aimed at identifying drugs that restore barrier function.